Consumer acceptability test on the organoleptic factors of dedawang pindang fish in Dedawang Hamlet, Bawean Island, Indonesia - Soedrijanto, Angky; Istiqomah, Titis; Rizkina, Fitriana Dina (Torani Journal of Fisheries and Marine Science, 2021)
This study aims to measure the level of consumer preference for organoleptic factors of pindang fish produced from the traditional scavenger business of Dedawang Hamlet, Telukjati Dawang Village, Tambak Sub-district, Bawean Island - Gresik Regency.The research was conducted from July to September 2020 involving 221 respondents from various backgrounds as panelists to assess the level of preference for pindang fish. The test material came from one of the scaling efforts carefully selected by the researcher. The organoleptic test includes 8 (eight) things, namely: taste, deviated odor (indication of deterioration), specific aroma, color, appearance, consistency, packaging aesthetics, and durability. The results showed that the durability factor (score 93.57), product aesthetics (score 90.48), smell (score 86.35), and distinctive aroma (score 81.35) were the main attractions for consumers buying pindang fish. While the appearance (score 53.07), consistency (score 63.51), color (score 65.41), and taste (score 68.17) are things that need to be improved to increase attractiveness to consumers. Keywords: organoleptic, pindang, consumer acceptability